Optimizing the planning and logistic of IBC usage in pharmaceutical industry - Chen, Xiaowen (2014)
This study studies the planning and logistics issues for a pharmaceutical company ABC concerning Intermediate Bulk Containers (IBCs), which are expensive equipment used to contain and transport raw materials and semi-finished products. Due to the high price of IBCs, company ABC sought to minimize the number of IBCs needed to support the production of four different types of products. In the first stage of this study, five drivers that affect the number of IBCs required were identified. Deterministic optimization models were developed to calculate the minimum number of IBCs needed for each product given the production plan for 2009. A cleaning schedule for IBCs was proposed accordingly to maximally reuse IBCs. The second stage of this study considers stochastic factors into the number of IBCs decision making process. Given the complexity associated with multiple product types and production processes, a simulation model is constructed with ProModel to analyse IBC usage under different scenarios. Design of experiment was applied for data analysis and for quantifying the effects of random events. The models developed in this study provide a scientific basis for planning IBC usage and are adopted by the company for their operations.